Imagined Embedding(s): Young People’s Reasons for Moving to Norway - Tuba Ardic (Social Sciences, 2023)
There has been a plethora of scholarly work which examines the motivational and lingering factors of youth mobilities but there has not been a sufficient number of scholarly articles that explain specifically why Norway is a destination for youth, with a few exceptions. This paper focuses on young people who move to Norway for employment reasons. Six interviews were chosen via a purposeful sampling from a sample of 15 interviewees, who moved to Norway. The interviews were transcribed and were analysed via thematic analysis. As a result of the thematic analysis, it is observed that imagined embedding(s), a theorisation to explain the motivations to choose a destination place, can be applied to these cases. I contribute to the literature by applying imagined embedding(s) to the motivations for moving abroad, in this case to Norway for young people in mobility. Since most of the work examines the embedding(s) during mobility, my focus will be on the period before mobility and the initial period of mobility. This research proves that the economic reasons for movement are almost always coupled with other more intrinsic and non-economic motives and imagination(s) of a place.